Students’ Practices of 21st Century Skills between Conventional learning and Blended Learning - Hadiyanto, Hadiyanto; Failasofah, Failasofah; Armiwati, Armiwati; Abrar, Mukhlash; Thabran, Yulhenli (Journal of University Teaching and Learning Practice, 2021)
The application of blended learning in higher education has practically increased through the years, this is however aimed to develop the students rare 21st century skills. Furthermore, the present study investigates the differences in learning process across one semester, and the research design comprised of quasi experimental method without conducting any pre-test, particularly for the conventional and blended learning class. Therefore, self-evaluation questionnaire on 21st century skills were distributed, and the experimental outcome revealed the significant skill practice performed by students in blended learning classes compared to the counterparts in conventional programmes. This learning method was assessed to contain soft and hard skills, in addition to an increased GPA. The aim of this study, therefore, is to investigate the impact of blended learning in course application, with the goal of optimizing students’ 21st century skills and GPA.